(untitled) (Delta Medical College Journal, 2020)
Background: Diabetic foot is a common and potentially disastrous complication that can rapidly progress to irreversible septic gangrene, necessitating foot amputation. Objectives: To assess the clinical outcome of treatment of diabetic foot in diabetic patients based on random blood glucose (RBG) and HbA1c level. Materials and method: This prospective observational study was conducted in the Department of Surgery, BIRDEM General Hospital, Shahbag, Dhaka, Bangladesh, from July 2018 to December 2018. A total of 350 patients with diabetic foot were enrolled in the study based on inclusion and exclusion criteria. The patients were divided into four groups based on RBS and HbA1c level. A complete history was taken, thorough clinical examination was done and relevant investigation reports were collected. Collected data were classified, edited, coded, and entered into the computer for statistical analysis using SPSS version 23. Results: Mean age was 47.6±13.3 years in group A, 48.2±12.7 years in group B, 46.7±13.1 years in group C, and 49.9±12.5 years in group D. Male to female ratio was 2.3:1 in group A, 3.5:1 in group B, 1.5:1 in group C and 2.9:1 in group D. One hundred eight patients were found to have Wagner ulcer grading I. Among them, 2(20.0%) were in group A, 9(33.3%) were in group B, 12(36.4%) were in group C, and 85(30.4%) were in group D. Twenty-two patients were found to have Wagner ulcer grading IV. Among them, 1(3.0%) of group C and 21(7.5%) of group D. The difference was statistically significant (p<0.05) among the four groups. Two hundred eighty-eight patients had wound healing time of 2-6 weeks. Among them were 1(10.0%) in group A, 25(92.6%) in group B, 29(87.9%) in group C, and 233(83.2%) in group D. The mean wound healing time was found to be 1.5±0.7 weeks in group A, 3.1±1.3 weeks in group B, 3.6±1.2 weeks in group C and 4.9±1.8 weeks in group D. The difference was statistically significant (p<0.05) among four groups. One hundred six patients underwent amputation at a different level. Among them, 1(10.0%) in group A, 5(18.5%) in group B, 13(39.4%) in group C and 87(31.1%) in group D. The difference were not statistically significant (p>0.05) among four groups. Conclusion: Elevated HbA1c was associated with slower and incomplete foot healing in diabetic patients. Random blood glucose and HbA1c parameters can be used as dependable predictors of foot ulcer healing in the diabetic patients. Delta Med Col J. Jul 2020;8(2): 86-92